Crowding auditivo : o impacto dos estímulos sonoros sobre a relação entre densidade humana e percepção de crowding - Deyl, Fernanda Trindade (2020)
Crowding is one of the key elements present in the physical retail environment which influences consumer behavior. Through the study of the phenomenon, we seek to understand how consumers react to situations of high density in the consumption environment. Crowding is an interesting phenomenon because it is a dynamic environmental factor, as the number of customers in a consumer environment can vary throughout the day. In addition, store density can influence the perception of other factors present in the environment. Studies have already shown that, for practical purposes, it is important for managers to understand how perceived crowding affects the consumer's shopping experience in order to reduce its negative effects. Therefore, it is important to explore and understand the phenomenon under a multisensory approach, investigating all sensory stimuli that can generate perception of high density and consequent discomfort. It is noticed, then, that the literature produced on the subject so far emphasizes, for the most part, the visual perspective of crowding, treating it as a phenomenon based on stimuli captured by vision. Given its importance for communication with consumers and the ease in manipulating sound stimuli present in a retail environment, hearing stands out as a potential perspective for investigating the phenomenon in regard to the study of consumer behavior. Through the conduction of two experimental studies, the present thesis investigates the influence of sound stimuli representative of human density on perceived crowding, demonstrating that the visual and auditory (in)congruence perceived by consumers moderates this relationship. In addition, the results indicate that the effect of human density is mitigated in situations in which incongruence between visual and sound stimuli is perceived. Therefore, it appears that both human density and perceived crowding can be measured through sound stimuli, demonstrating that there is an auditory dimension to the phenomenon. Thus, the concept of auditory crowding is proposed. Furthermore, the study explores in greater detail the mechanisms through which auditory stimuli affect the relationship between human density and perceived crowding, demonstrating that the emotions of pleasure and arousal mediate such relationship, and that the isolated sound stimuli of human density have an effect on the emotions felt by consumers during the shopping experience.